2017
DOI: 10.1111/ijn.12561
|View full text |Cite
|
Sign up to set email alerts
|

Helping Babies Breathe implementation in Zanzibar, Tanzania

Abstract: Results indicate that participants retained knowledge and skills and used them in clinical practice. Observations demonstrated that participants took appropriate actions when presented with a baby who was not breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Birth asphyxia and failure to initiate or sustain resuscitation at birth remain the main causes of neonatal deaths worldwide (9). These data are even higher in rural locations, such as in Zanzibar hospitals, where up to 60% of neonatal deaths occur (10,11). A survey study in five rural districts of southern Tanzania identified 219 neonatal deaths (12).…”
Section: Introductionmentioning
confidence: 99%
“…Birth asphyxia and failure to initiate or sustain resuscitation at birth remain the main causes of neonatal deaths worldwide (9). These data are even higher in rural locations, such as in Zanzibar hospitals, where up to 60% of neonatal deaths occur (10,11). A survey study in five rural districts of southern Tanzania identified 219 neonatal deaths (12).…”
Section: Introductionmentioning
confidence: 99%
“…There are many potential influencers of these results. Trainings were led by local leaders with prior experience teaching HBB in Zanzibar [8]. All master trainers were midwives delivering babies in the facilities of interest.…”
Section: Key Resultsmentioning
confidence: 99%
“…A team with a small budget, local leadership and buy-in will likely be able to yield a positive impact on care of neonates through a similar implementation of HBB in a like environment. Other HBB implementations with similar strategy have also yielded positive results [8,12,17]. The limitations are acknowledged and will provide a framework to build on going forward.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Helping Mothers Survive (HMS) is a simulation-based training curriculum developed by Jhpiego in collaboration with global partners, with the goal of combating maternal mortality through the improvement of maternal care skills among local healthcare workers. Helping Mothers Survive was modeled after the Helping Babies Breathe (HBB) training program, which has been shown to improve birth attendants' neonatal resuscitation knowledge and skill levels as well as decrease infant mortality in various low-resource settings (9)(10)(11). Helping Mothers Survive is composed of four training modules focusing on PPH, pre-eclampsia/eclampsia, essential care for labor and birth, and threatened preterm birth care (12).…”
Section: Introductionmentioning
confidence: 99%